2013
DOI: 10.1111/nuf.12048
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse-Led Wellness Program for Migrant Backstretch Workers

Abstract: Through multi-agency collaboration, continued development, and revision of strategies, health enhancement and disease prevention are accessible to vulnerable migrant workers. Faculty, students, and staff work with clients to provide quality health education programs, screenings, and referrals to improve their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Bailey and Dougherty's research revealed similar results after conducting a needs assessment of backstretch workers at a Pennsylvania thoroughbred racetrack. [5] Findings indicated that common issues in this population included work-related physical injuries and chronic, noninfectious diseases including diabetes and hypertension. Other significant areas of concern identified a of a need for bilingual communication between nursing staff and clients, access to healthcare services, women's healthcare issues, and improvement in nutritional status.…”
Section: Introduction 11 Vulnerable Populations' Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Bailey and Dougherty's research revealed similar results after conducting a needs assessment of backstretch workers at a Pennsylvania thoroughbred racetrack. [5] Findings indicated that common issues in this population included work-related physical injuries and chronic, noninfectious diseases including diabetes and hypertension. Other significant areas of concern identified a of a need for bilingual communication between nursing staff and clients, access to healthcare services, women's healthcare issues, and improvement in nutritional status.…”
Section: Introduction 11 Vulnerable Populations' Overviewmentioning
confidence: 99%
“…Multiple factors impeding women's care relate to cultural norms, religious or spiritual beliefs, chronic poverty, lack of health insurance, transportation, knowledge deficit, confidentiality, and psychological factors including embarrassment and the fear of cancer. [5,13,14] Language barriers and migratory patterns also are aspects that create barriers to women's health. [5,13,14] Fear of retribution for taking time off from work to seek procedures further delay mammography and PAP screenings.…”
Section: Introduction 11 Vulnerable Populations' Overviewmentioning
confidence: 99%
See 3 more Smart Citations